Influenza Virus Vaccine Based on the Conserved Hemagglutinin Stalk Domain - John Steel (American Society for Microbiology, 2010)
ABSTRACT Although highly effective in the general population when well matched to circulating influenza virus strains, current influenza vaccines are limited in their utility due to the narrow breadth of protection they provide. The strain specificity of vaccines presently in use mirrors the exquisite specificity of the neutralizing antibodies that they induce, that is, antibodies which bind to the highly variable globular head domain of hemagglutinin (HA). Herein, we describe the construction of a novel immunogen comprising the conserved influenza HA stalk domain and lacking the globular head. Vaccination of mice with this headless HA construct elicited immune sera with broader reactivity than those obtained from mice immunized with a full-length HA. Furthermore, the headless HA vaccine provided full protection against death and partial protection against disease following lethal viral challenge. Our results suggest that the response induced by headless HA vaccines is sufficiently potent to warrant their further development toward a universal influenza virus vaccine. IMPORTANCE Current influenza vaccines are effective against only a narrow range of influenza virus strains. It is for this reason that new vaccines must be generated and administered each year. We now report progress toward the goal of an influenza virus vaccine which would protect against multiple strains. Our approach is based on presentation to the host immune system of a region of the influenza virus—called a “headless hemagglutinin” (headless HA)—which is similar among a multitude of diverse strains. We show that vaccination of mice with a headless HA confers protection to these animals against a lethal influenza virus challenge, thereby demonstrating the viability of the approach. Through further development and testing, we predict that a single immunization with a headless HA vaccine will offer effective protection through several influenza epidemics.